China and a Global Green System of Innovation - Marinova, Dora; Guo, Xiumei; Wu, Y. (International Association of Impact Assessment, 2012)
The evidence provided by the science of climate change has triggered heated political discussion and a variety of economic measures aimed at reducing humanity’s ecological footprint. New sustainable technologies, including renewable energy, are paving the way for community values to encourage greater sustainable behaviour but technology impact assessment needs to be internalised in the innovation cycle in order to prevent humanity getting locked in other challenges similar to climate change. There are encouraging calls for sustainability to become the main focus of economic development. We describe this shift as a transition towards a global green system of innovation (GGSI). China’s contribution to the current environmental state of the planet is enormous, but so is its potential for decarbonising the country’s economy. The paper analyses recent trends and concludes that for China to play an active role in the changing global attitudes and the shift towards a global green system of innovation, it must become a leader in major institutional transformation including the development of education, public participation and governance. It also outlines why it’s unlikely that China will fulfil this role based on adopting a western type consumerist society, as well as provides a suggested approach for China, to focus on building balanced strategies that are representative of long-lasting Chinese cultural values.